Jewish life in Renaissance Italy - Bonfil, Robert (University of California Press, 1994)
With this heady exploration of time and space, rumors and silence, colors, tastes, and ideas, Robert Bonfil recreates the richness of Jewish life in Renaissance Italy. He also forces us to rethink conventional interpretations of the period, which feature.